2012
DOI: 10.1111/j.1471-0528.2012.03408.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pharmacotherapy for smoking cessation among pregnant smokers: a meta‐analysis

Abstract: Background The efficacy and safety of pharmacotherapy for smoking cessation among pregnant smokers has not yet been established.Objective To investigate the efficacy and safety of pharmacotherapy for smoking cessation among pregnant smokers.Search strategy A search was made of PubMed, Embase and CENTRAL in June 2011.Selection criteria Randomised controlled trials (RCTs), quasiRCTs and retrospective or prospective controlled studies were included.Data collection and analysis The main analyses were designed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 25 publications
2
31
0
Order By: Relevance
“…13 A review of Nicotine Replacement Therapy (NRT) reported no difference in symptoms such as headache, skin irritation, dizziness, nausea, heartburn, fatigue, palpitation, reduced sensation, increased morning sickness symptoms, and aggravation of postnatal depression, compared to the placebo groups. 14 Conversely, there was some evidence that positive outcomes such as higher mean birthweight and lower preterm delivery occurred in the NRT group. Stronger evidence is required but current data indicates that NRT in pregnant women is safe and could result in higher mean birth weights and lower rates of preterm delivery.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…13 A review of Nicotine Replacement Therapy (NRT) reported no difference in symptoms such as headache, skin irritation, dizziness, nausea, heartburn, fatigue, palpitation, reduced sensation, increased morning sickness symptoms, and aggravation of postnatal depression, compared to the placebo groups. 14 Conversely, there was some evidence that positive outcomes such as higher mean birthweight and lower preterm delivery occurred in the NRT group. Stronger evidence is required but current data indicates that NRT in pregnant women is safe and could result in higher mean birth weights and lower rates of preterm delivery.…”
Section: Editorialmentioning
confidence: 99%
“…14 Similarly, a systematic review 15 investigating NRT as an adjunct to behavioural support found that when studies without randomization were excluded, there was no significant difference between the smoking cessation rate for the NRT and the placebo group. The low adherence rate in the treatment group may explain these results and may have occurred because the mothers perceived NRT to be harmful to the foetus.…”
Section: Editorialmentioning
confidence: 99%
“…weight with nicotine replacement therapy, one of which also found decreased incidence of low birth weight and preterm delivery with therapy (27). For pregnancy, transdermal nicotine is classified as FDA Category D, and shorteracting therapies are classified as FDA Category C. Nicotine concentrates in breast milk, with a 2.9:1 ratio with maternal serum (28).…”
Section: Key Points/clinical Pearlsmentioning
confidence: 99%
“…2 First, we are very sorry that we did not include in our review Coleman et al's review, 3 which was published in early 2011. We should have searched and reviewed previous literature on this issue more thoroughly.…”
Section: Sirmentioning
confidence: 99%